Adjusment of Students in Islamic Boarding Schools - M. Agung Rahmadi; Helsa Nasution (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to describe the student adjustment in the Islamic boarding school. This adjustment is divided into two aspects: personal and social adjustments. This study used a quantitative descriptive method. The research population was 2,695 students of class 1 in Musthafawiyah Islamic Boarding School Purbabaru. The sample chosen was 349 students selected by using the proportional random sampling technique. The data were collected by using instruments and analyzed by using the descriptive method. The results indicated that the student self-adjustment is in a good category. Thus, the students are able to adapt to themselves and socially so that they feel satisfied with themselves and their environment.